Use and costs of services and unpaid care for people with mild‐to‐moderate dementia: Baseline results from the IDEAL cohort study - Catherine Henderson; Martin Knapp; Sharon M. Nelis; Catherine Quinn; Anthony Martyr; Yu‐Tzu Wu; Ian R. Jones; Christina R. Victor; James A. Pickett; John V. Hindle; Roy W. Jones; Michael D. Kopelman; et al. (Alzheimer’s & Dementia: Translational Research & Clinical Interventions)
Abstract Introduction We examined 3‐month service use and costs of care for people with mild‐to‐moderate dementia in Great Britain. Methods We analyzed Improving the experience of Dementia and Enhancing Active Life cohort study baseline data on paid care, out‐of‐pocket expenditure, and unpaid care from participants with dementia (N = 1547) and their carers (N = 1283). In regression analyses, we estimated per‐group mean costs of diagnostic and sociodemographic subgroups. Results Use of services apart from primary and outpatient hospital care was low. Unpaid care accounted for three‐quarters of total costs (mean, £4008 [standard error, £130] per participant). Most participants (87%) received unpaid care equating to 36 hours weekly. Estimated costs for people with Parkinson's dementia were £8609, £4359 for participants with mixed dementia, and £3484 for those with Alzheimer's disease. Total costs were lower for participants with dementia living alone than living with others (£2484 vs. £4360); costs were lower for female than for male participants (£3607 vs. £4272). Discussion Costs varied by dementia subtype, carer status, and living arrangement. Policy makers should recognize the high costs of unpaid care for people with dementia, who do not always get the support that they need or would like to receive.